Potensi Ekstrak Moringa Oleifera Untuk Mengatasi Gastroenteritis Bakteri: Pemanfaatan herbal dalam tindakan preventif, kuratif, dan rehabilitatif penyakit gastrointestinal pada komunitas agrikultur - Yemima Billyana Kusbijantoro; Nabila Atika Naufizdihar; Arga Setyo Adji (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2022)
ABSTRACT Bacterial gastroenteritis is a disease in the tropics in the form of inflammation of the stomach and intestines due to several bacteria, such as Salmonella,Campylobacter, Shigella, E. coli, Vibrio, Yersinia, and Listeria with symptoms of diarrhoea without or with vomiting, and frequent fever. Gastroenteritis is a global disease with the highest prevalence in the agricultural community, especially farmers and fishermen. This reasearch to determine the potential of leaf and seed extract Moringa oleifera as an alternative therapy for bacterial gastroenteritis. Methods: The journal writing method uses a literature review approach derived from the analysis and synthesis of various related references. The author selects journals full text and books published in the last ten years maximum through several databases, namely PubMed, Google Scholar, Science Direct, and Cochrane with the keywords: diarrhoea, gastroenteritis, and Moringa oleifera. Results: seed and leaf extract Moringa oleifera played a role in preventing some of the effects of the pathogenesis of diarrhoea due to bacterial infection. Methanol, N-hexane, ethyl acetate, flavonoids, phenols, saponins, alkaloids, tannins, and steroids from seed and leaf extract Moringa oleifera have antibacterial effects. The content of quercetin has an anti-inflammatory effect. The content of tannins, flavonoids, and alkaloids has antidiarrheal activity. The content of ethanol and tannins has an antiulcer effect. This potential can help cure patients with bacterial gastroenteritis.